2009
DOI: 10.1002/ijc.24682
|View full text |Cite
|
Sign up to set email alerts
|

Active MMP‐2 effectively identifies the presence of colorectal cancer

Abstract: Fully active MMP-2 is expressed at such low levels in human tissues that studies often fail to confirm its value as a cancer marker despite strong associations with malignancy. Our study utilized careful extraction, accurate activity measurements, standardization to purified controls and a new statistical metric to determine whether active MMP-2 is an effective indicator of colorectal cancer compared to pro-MMP-2 or pro-MMP-9. MMP-2 and MMP-9 activities were analyzed in matched normal and cancer samples from 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 34 publications
4
32
1
1
Order By: Relevance
“…MMP2 and MMP9 are known for their ability to degrade native type IV collagen [40] and related to metastasis while MT1-MMP is a physiologic activator of proMMP2. Active MMP2 was highly expressed in cancer samples while it was very low or not detectable in normal tissues [41,42]. The ALG bead-cultured MHCC97L and HCCLM3 cells, as well as liver cancer tissue, had constantly higher gene expression of MMP2, MMP9 and MT1-MMP compared with adhesion cells (Figs.…”
Section: Discussionmentioning
confidence: 92%
“…MMP2 and MMP9 are known for their ability to degrade native type IV collagen [40] and related to metastasis while MT1-MMP is a physiologic activator of proMMP2. Active MMP2 was highly expressed in cancer samples while it was very low or not detectable in normal tissues [41,42]. The ALG bead-cultured MHCC97L and HCCLM3 cells, as well as liver cancer tissue, had constantly higher gene expression of MMP2, MMP9 and MT1-MMP compared with adhesion cells (Figs.…”
Section: Discussionmentioning
confidence: 92%
“…The gellatinases MMP-2 and MMP-9 have been studied in this regard because of their specificity for breaking down the collagen of basement membranes [39]. It has been proved that these enzymes are involved in the development of many malignant neoplasms: gastric, colorectal, pancreatic and breast cancer [40][41][42][43]. High MMP-9 protein expression in tumor tissues of EC patients has been shown in several studies [4,18,[44][45][46][47].…”
Section: Mmp-9mentioning
confidence: 99%
“…It was shown that degradation of basement membrane and invasion of epithelium is the first step of tumor development and metastasis [10]. www.fhc.viamedica.pl It was proved that matrix metalloproteinase 2 (MMP-2) and tissue inhibitor of matrix metalloproteinases 2 (TIMP-2) are involved in tumor invasion and metastasis in case of breast, gastric, pancreatic and colorectal cancer [11][12][13][14]. It was also suggested, that MMP-2 might play an important role in carcinogenesis of esophageal squamous cell cancer (ESCC) and could act as a biological marker of invasion and lymph node metastasis in this type of tumor.…”
Section: Introductionmentioning
confidence: 99%